Тимур и его команда - Гайдар Аркадий Петрович (Школьная библиотека, 2012)
Экземпляры: ф-4 (20210811) / Инвентарный номер: 57285 / Цена: 110.00 / Сис.шифр: Р2 / Авт.знак: Г 14 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6